A novel sustainable platform for scaled manufacturing of double‑stranded RNA biopesticides - Nwokeoji, A.O.; Nwokeoji, E.A.; Chou, T.; Togola, A. (Springer, 2022)
RNA interference (RNAi) represents one of the most conserved pathways evolved by eukaryotic cells for regulating gene expression. RNAi utilises non-translatable double-stranded RNA (dsRNA) molecules to sequester or degrade mRNA molecules gene. In RNAi, specifically designed exogenous dsRNA delivered to the cell can silence a target gene, a phenomenon that has been exploited in many functional studies and explored in biopesticide applications. The search for safe and sustainable crop pest management options drives the need to offset the effect of inorganic pesticides on biodiversity. The prospect of replacing inorganic pesticides with dsRNA crop spray is gaining popularity, enhanced by its high-target specificity and low environmental impact. However, for dsRNA to reach the pesticide market, it must be produced cost-effectively and sustainably. In this paper, we develop a high-yield expression media that generates up to 15-fold dsRNA yield compared to existing expression media utilising 1 mM IPTG. We also optimise a low-cost purification method that generates high-quality and purified dsRNA. The developed method circumvents the need for hazardous chemical reagents often found in commercial kits or commercial nucleases to eliminate contaminating DNA or single-stranded RNA (ssRNA) species. We also demonstrate that the production platform is scalable, generating 6.29 mg dsRNA from 259 mg wet E. coli cell pellet. The results also provide structural insights into the heterogeneous dsRNA species within the microbial-derived dsRNA pool. Finally, we also show that the purified ‘naked’ dsRNA, without prior formulation, can induce insect toxicity under field conditions. This study provides a novel, complete, low-cost process dsRNA platform with potential for application in industrial dsRNA production.